The influence of a congested calendar on physical performance in elite soccer - lago-Penas, C.; Rey, E.; Lago-Ballesteros, J.; Casais, L.; Dominguez, E. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to investigate recovery via analysis of activity profiles in a professional soccer team over an intense period of matches. A total of 172 outfield players from 27 Spanish League matches played by a professional team during the 2005-2006 season were analyzed using a multiple-camera match analysis system. The dependent variables were the distance covered by players at different intensities. Data were analyzed using an independent-sample t-test and a linear regression analysis with 5 independent variables: the number of matches played per week (1 or 2), match status (i.e., whether the team was winning, losing or drawing), match location (i.e., playing at home or away), quality of the opponents (strong or weak), and the individual playing position of the players. The main finding of this study suggests that the activity profiles of professional soccer players were not influenced by short recovery between matches. Although those players who played 2 matches a week covered less distance at maximal (>23 km/h), submaximal (19.1-23 km/h), and medium (14.1-19 km·h-1) intensities than those players who played 1 match a week, no significant differences were found. Moreover, results from this study seem to confirm that the elite soccer players` distance covered at various speeds is dependent on match contextual factors. The top-class players performed less high-intensity activity (>19.1 km/h) when winning than when they were losing (p < 0.05), but more distance was covered by walking and jogging when winning (p < 0.05). The home teams covered a greater distance than away teams at low intensity (<14.1 km/h) (p < 0.01). Finally, the better the quality of the opponent, the higher the distance covered by walking and jogging.